Characterization of the geological and geotechnical properties of soil using the surface wave approach - Oloye, Oluwatobi; Adepelumi, Adekunle (International Journal of Advanced Geosciences, 2015)
As part of the efforts to examine the elastic and engineering properties of the subsurface sequence at a proposed new power plant site in Edo State, a geophysical survey involving Multichannel Analysis of Surface Waves (MASW) was carried out. The MASW was adopted to determine the vertical and lateral variations in velocity beneath each seismic line. The MASW was carried out on two seismic lines each trending NE-SW. A geophone interval of 3 m was used, and the length of the seismic lines ranged from 60 – 90 m. The ES-3000 seismograph was used for the surface wave data acquisition and the Shear-Wave velocity structures of the area were obtained through the inversion of the acquired surface wave data. The one dimensional (1D) S-Wave velocity profiles along the lines were diagnostic of generally low velocity lithologies that suggest sand, clayey sand and sandy clay formations with relatively varying thicknesses. The subsurface layers delineated had shear-wave velocity values in the range of 63-400 m/s. They were classified using the NEHRP Seismic Site Classification, and all of them were in the range of stiff soil to soft clay soil. The bulk moduli (k) for these soils were in the range of 3.22-3.98 GPa. This depicts relatively low strength of the subsurface materials. The shear moduli (μ) values range from 7.15-7.43 MPa, which is indicative of low to moderate strength. The information provided in this study will aid the structural engineer or architect in foundation design of the proposed power plant. From the results of this study, it is concluded that although the subsurface layers are of relatively low strength, with the right intervention of the civil engineer, a suitable foundation can be designed for the gas plant.